ASAL USUL DAN MAKNA NAMA GELAR DATUAK DI NAGARI NAN TUJUAH KECAMATAN PALUPUH KABUPATEN AGAM - Amrizal Amrizal (Universitas Andalas, 2011)
This study reviews the meaning of datuak title as an elder (penghulu) in Nagari Nan Tujuah, Palupuh Agam which based on the traditional proverb